Impact of sarcopenia on rehabilitation outcomes after total knee replacement in older adults with knee osteoarthritis - Chun-De Liao; Hung-Chou Chen; Shih-Wei Huang; Tsan-Hon Liou (Therapeutic Advances in Musculoskeletal Disease, 2021)
Introduction: Knee osteoarthritis (KOA) is associated with an increased risk of sarcopenia, and aging-related muscle deterioration continues after total knee replacement (TKR). Low skeletal muscle mass index may influence postoperative rehabilitation outcomes. Through this study, we aimed to investigate the impact of preoperative sarcopenia on clinical outcomes after postoperative rehabilitation in older Asian adults. Methods: A total of 190 older adults (39 men, 151 women) were enrolled from two previous trials and were classified as having no sarcopenia, class I sarcopenia, or class II sarcopenia according to definitions provided by the Asian Working Group for Sarcopenia (AWGS) and the European Working Group on Sarcopenia in Older People (EWGSOP). All patients were retrospectively analyzed before (T 0 ) and after (T 1 ) TKR rehabilitation and 10 months after surgery (T 2 ). The outcome measures included the timed up-and-go test (TUGT), gait speed (GS), timed chair rise (TCR), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and physical difficulty (WOMAC-PF). With patient characteristics and T 0 scores as covariates, an analysis of variance was performed to identify intergroup differences in changes of all outcome measures at T 1 and T 2 . Results: According to the definitions of both the AWGS and EWGSOP, patients with class I and class II sarcopenia exhibited minor changes in TUGT, GS, TCR, and WOMAC-PF at T 1 and T 2 (all p  < 0.05), compared with those without sarcopenia. For patients classified as having sarcopenia based on AWGS and EWGSOP definitions, no significant intergroup differences in WOMAC pain score was observed at T 1 or T 2 (all p  > 0.05). Conclusions: Sarcopenia independently had negative impacts on the treatment effects of rehabilitation on physical mobility but not on pain outcome after TKR in older adults with KOA.